Timing of stillbirth and neonatal death during 2000 to 2007 in the UK. (7th June 2011) - Springett, A; Sullivan, A; Stephens, I; Golightly, S; Dorling, J
Abstract : Background and aims: There has been much interest in increasing staff cover across the week both in labour wards and in neonatal units with the hope that this will improve pregnancy outcomes. CMACE collects information on all stillbirth and neonatal deaths across the UK and analysed the pattern of deaths across the 24 h time period and between different days of the week to see if there are times that staff might be targeted towards. Methods: 8 years (2000–2007) Data on all UK stillbirths and neonatal deaths including the date and time of birth were collected by CMACE. Missing and denominator data was obtained from the Office of national statistics. Results: A clear diurnal pattern of stillbirths was demonstrated with a nadir of 3% of stillbirths occurring per hour between 07:00 and 10:00. This rises in the late afternoon and evening to a peak of approximately 5% of stillbirths per hour between 14:00 and 20:00. No such association with time of birth was seen for neonatal deaths and intrapartum related deaths. Intrapartum death was however more common on Thursdays and Fridays. Conclusions: Stillbirths were more common in number during the later afternoon and evening. The underlying causes of these findings are likely to be multifactorial and complex but warrant further examination. In particular, further research to explore the relationship of staffing availability to the timing of stillbirths may be especially beneficial either to reduce stillbirths or save staffing costs.